Analisis Skala Student Well-Being Versi Indonesia pada Mahasiswa dengan Rasch Mixture Model - Putri, Erlavianda Tarita; Aprilianto, Khoifulloh; Yudiarso, Ananta (Personifikasi: Jurnal Ilmu Psikologi, 2025)
This study evaluates the psychometric properties of the Indonesian Student Well-Being Scale (Aprilianto, 2023), grounded in Fraillon (2004) theory, using a quantitative validation design with data from 510 university students aged 19-25  collected through accidental sampling. The scale, initially comprising 53 items, was refined to 41 items after removing non-fitting items based on Rasch and Mixture Rasch Model (MRM) analyses. Results demonstrated the scale's unidimensionality, high reliability (Cronbach's alpha 0.9), and valid measurement properties, with MRM identifying two latent classes reflecting demographic differences. The scale effectively measures intrapersonal and interpersonal dimensions using a 4-point Likert scale. However, it underrepresents extremely high well-being levels, highlighting the need for additional item development. Despite its strengths, future studies should explore broader demographic variables, including cultural and socioeconomic factors, to enhance the scale's applicability and depth.